Clustering of banks by the level of digitalization in the context of the COVID-19 pandemic - Kolodiziev, Oleh; Shcherbak, Valeriia; Vzhytynska (Omelchenko), Kseniia; Chernovol, Olena; Lozynska, Olha (My University, 2022)
The COVID-19 pandemic has complicated the operating environment for banks around the world. Determining the drivers of digitalization of banking services based on the principles of corporate social responsibility of banks makes it possible to find a way out of the crisis. The objective of the study is to develop a model for clustering banks in terms of the level of digitalization on the principles of corporate social responsibility. In this study, a twofold model has been proposed: the first part includes the calculation of the level of digitalization of banking, and the second part includes mathematical simulation of the clustering of bank digitalization level. This study reveals new possible solutions to the digitalization of banking in the face of new threats. In particular, factor analysis identifies the main factors, cluster analysis ranks banks into three categories (A, B, C) of service digitalization, and a dendrogram identifies digitalization drivers. The model was tested on 22 banks. Eight per cent of the banks are rated A “Very good” and B “Good”. 92% have Level C “Satisfactory”. The results of the study prove that the model should be validated. It should be confirmed that the application of the developed methodology for increasing the digitalization of banking services will increase customer loyalty by 15%, improve sustainability by reducing risk by 10%, and make banks attractive for investment by 15-20%.
Keywords: digitalization; corporate social responsibility; digital banking; coronavirus; діджиталізація; корпоративна відповідальність; діджитальний банкінг; коронавірус; кафедра економічної теорії